PERKEMBANGAN DAN KONTRIBUSI SUBSEKTOR PERIKANAN TERHADAP PDRB KABUPATEN ROKAN HILIR, RIAU - Ramli, M. (Jurnal Perikanan dan Kelautan, 2013)
The study aims to assess the development and fisheries subsector contribution tothe economy (GDP) Rokan Hilir district. In order to achieve these objectives, the an-nual data collected (series) GDP and fisheries data Rokan Hilir district during the peri-od 2006 to 2010. Based on these data, the fisheries sector contributed 21.62%. Andseen his contribution to the fellow agriculture, fisheries subsector is the largest contrib-utor (41%) among the other sub-sectors (crops and hotikultura, tree crops, livestock,and forestry). Fisheries in Rokan Hilir district dominated by fishing in the ocean. Fish-eries production in 2010 was recorded 59808.43 tons, up from the previous years pro-duction. The increase in production occurred primarily in aquaculture production.